2019
DOI: 10.1080/16549716.2019.1670033
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of health promotion regarding diet and physical activity among Nepalese mothers and their young children: The Heart-health Associated Research, Dissemination, and Intervention in the Community (HARDIC) trial

Abstract: Background: Nepal, like many low-and middle-income countries, exhibits rising burden of cardiovascular diseases. Misconceptions, poor behavior, and a high prevalence of risk factors contribute to this development. Health promotion efforts along with primary prevention strategies, including risk factor reduction in both adults and children, are therefore critical. Objectives: This study assessed the effectiveness of a health promotion intervention on mothers' knowledge, attitude and practice (KAP) and their chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Most studies focus on nutrition education for parents or educational programs targeting both preschoolers and their parents [ 26 , 27 ], but there is a general scarcity of research on nutrition education for 3- to 6-year-olds whose eating habits and food preferences are easily modified through imitation and group learning. Healthy eating habits that have been instilled in the preschool period affect later stages of life and minimize the risk of nutrition-related problems in adulthood, because nutrition affects a child’s physical, social and emotional development as well as behavior [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focus on nutrition education for parents or educational programs targeting both preschoolers and their parents [ 26 , 27 ], but there is a general scarcity of research on nutrition education for 3- to 6-year-olds whose eating habits and food preferences are easily modified through imitation and group learning. Healthy eating habits that have been instilled in the preschool period affect later stages of life and minimize the risk of nutrition-related problems in adulthood, because nutrition affects a child’s physical, social and emotional development as well as behavior [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Nepal have shown differences in prevalence of overweight/obesity and diabetes between the ethnic groups. The highest prevalence has been reported in the Adhivasi/Janajati ethnic group [ 9 , 10 , 60 , 61 ]. Likewise, we observed that a higher proportion of women in this group had diabetes compared to the two other ethnicities, however, this was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant as nutrition educational interventions for providers caring for individuals with cirrhosis have been associated with a higher number of dietitian consultations, less days of inadequate nutrition, lower 90-day readmission rates, and improved quality of life and physical function [24]. Research outside of cirrhosis has similarly demonstrated that provider physical activity education can impact physical activity KAP scores [25,26], increase the frequency with which physical activity is prescribed, and improve appropriate referral rates [27]. Important to the feasibility of beginning to close this gap in care, providers in our study were keen to receive additional nutrition and physical activity training directed to cirrhosis.…”
Section: Discussionmentioning
confidence: 99%